Metode System Development Life Cycle dalam Perancangan Sistem Informasi Kuliah Kerja Kemasyarakatan - Hidayat, Taufik; Mobarrok, Abi; Sukisno, Sukisno; Nugroho, Asep Hardiyanto (Universitas Wahid Hasyim, 2024)
Our annual activity, Community Service Internship, will be conducted this semester. Previously, this reporting activity was carried out by sending pictures via WhatsApp. So, we created a reporting system to make it more efficient. Now, the reporting process will be handled through a website and monitoring will also be done through the website. This will make it easier for both participants and mentors to carry out the activity,